The theory of price - Stigler, George Joseph (New York : Macmillan, 1952)
The author seeks to emphasize the intimate relationship between theory and empirical evidence: how the theory is tested by evidence- not merely by logic- and how evidence instructs us on the forms of relationships.
First published in 1942 under title: The theory of competitive price.
Includes bibliographical footnotes and index.
rpm 24/01/2019
Loans
Keywords: Prices; Economics